A new strategy to synthesize three-coordinate mononuclear copper(i) halide complexes containing a bulky terphenyl bidentate phosphine ligand and their luminescent properties. (4th February 2019) - Liu, Li-Ping; Zhang, Rui; Liu, Li; Zhong, Xin-Xin; Li, Fa-Bao; Wang, Lei; Wong, Wai-Yeung; Li, Guang-Hua; Cong, Heng-Jiang; Alharbi, Njud S.; Zhao, Yi
Abstract : Three mononuclear three-coordinate Cu(i ) halide complexes were synthesized by a new strategy and they exhibit green to yellow green emission in the solid state at room temperature. Abstract : Highly emissive three-coordinate copper(i ) complexes have received much attention. Here, a new synthetic strategy for the preparation of a bulky terphenyl bidentate phosphine ligand mpdp is presented. A series of mononuclear three-coordinate Cu(i ) halide complexes [CuX(mpdp)] (mpdp = 4, 4′, 4′′, 5, 5′, 5′′–hexamethyl-(1, 1′:2′, 1′′-terphenyl)-2, 2′′-bis(diphenylphosphine), X = I (1 ), Br (2 ) and Cl (3 )), were synthesized. This method provides a three-coordinate linkage between the bulky bidentate phosphine ligand and CuX. These complexes exhibit green to yellow green emission in the solid state at room temperature and have peak emission wavelengths at 493–533 nm with microsecond lifetimes ( τ = 7.2–415.9 μs). Small S1 –T1 energy gaps in the solid state indicate that the emission occurs from a thermally activated excited singlet state at ambient temperature. The emission of complexes1–3 mainly originates from MLCT and XLCT transitions. The solution-processed devices of complex1 exhibit yellow emission with a CIE ( x, y ) of (0.44, 0.47).